How many people can you reach by public transport, bicycle or on foot in European cities? Measuring urban accessibility for low-carbon modes. - Poelman, Hugo; Dijkstra, Lewis; Ackermans, Linde (My University, 2020)
Good urban public transport can reduce congestion, air pollution and greenhouse gas emissions. It can improve a city’s quality of life and strengthen its economy. This working paper measures access to public transport for many European cities using the United Nations Sustainable Development Goal indicator. It shows that in virtually all cities at least 80 % of the population has easy access to public transport. In addition, it reveals that 56 % of an average city’s population has access to at least 10 departures an hour. Access to high-frequency departures is highest in cities with at least 1 million inhabitants and considerably lower in cities with fewer than 250 000 inhabitants, although some cities perform much better or worse than their size implies. a comparison between the population accessible by public transport with the nearby population in 42 cities shows that within 30 minutes people can only reach 24 % of the population living within a distance of 7.5 kilometres. Walking and cycling perform well in cities with dense road networks, higher densities and fewer steep slopes. Finally, the paper provides a set of context indicators to help to interpret the results, including the speed of public transport, vehicle kilometres travelled, building block size and density. To provide easy access to all this information, the working paper is accompanied by city fact sheets which report its various indicators and benchmark them to other cities.
Keywords: ÖPNV; Erreichbarkeit; Haltestelle; Fahrzeit; Reisezeit; Stadtverkehr; Internationaler Vergleich; Fallbeispiel; Benchmarking; Fußläufigkeit; Sustainable Development Goals